PEMANFAATAN UMKM PEBUATAN TAHU RUMAHAN MELALUI PENJUALAN MEDIA SOSIAL DI KOTA BIMA, JATIWANGI - Purnama, Ita; Fatihitul Mihrad; Ir Saputri; Yuliana (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Mr. Bambang's home tofu making UMKM is a producer of Bima tofu with the main ingredient being soybeans. Tofu is a processed product made from soybeans through a process of precipitation or coagulation by a coagulating agent. Soybeans have the advantage of being a good food product for increasing protein nutrition at a relatively cheap, practical and affordable price easily obtained. We are one of the STIE BIMA students who are engaged in developing tofu sales through social media. Mr. Bambang only processes one type of tofu, namely ordinary tofu. STIE BIMA students who participated directly in interviews and saw first hand how to make tofu, including soaking, washing, grinding, cooking, filtering, cutting and packaging. The materials for making student tofu are supporting materials. Quality control is carried out by the business owner on raw materials, production processes and final products to produce quality tofu.